Antioxidant Activity Of Jelly Candy From The Skin Of Red Dragons (Hylocereus spolyhizus) and Tomato (Lycopersicum esculentum Mill) - Jan Rudolf Assa; Teltje Koapaha; Enmia N. V. Boangmanalu (Jurnal Agroekoteknologi Terapan, 2022)
Free radicals are reactive species that can cause damage to body tissues and even cause many diseases. To neutralize free radicals in the body, antioxidants are needed. Many fruits found in Indonesia that contain antioxidants, including dragon fruit, the antioxidant content of dragon fruit is high. Jelly candy is a snack that is quite popular, especially for children. In general, the taste of jelly candy is obtained from essence which is a chemical. In this study, the taste of jelly candy was obtained from a combination of dragon fruit and tomatoes. The treatments in this study were the comparison of dragon fruit peel extract and tomato juice, including: Dragon fruit peel extract 100 g + 0 g tomato juice (A); Dragon fruit peel extract 25 g + 75 g tomato juice (B); Dragon fruit peel extract 50 + 50 g tomato juice (C); Dragon fruit peel extract 75 g + 25 g tomato juice (D); Dragon fruit peel extract 0 g + 100 g tomato juice (E). The results showed that the proportion of dragon fruit peel extract 100 g and tomato juice 0 g contained the highest total phenol in jelly candy, namely 15.2 mg GAE/g sample. The strongest antioxidant activity based on DPPH testing was found in the formula for mixing 0 g dragon fruit peel extract and 100 g tomato juice with IC50 = 203.69 ppm. Jelly candy with a proportion of 100 g of dragon fruit peel extract and 0 g of tomato juice contained the highest vitamin C of 0.455 mg/100 g sample. Keywords: Jelly Candy, Antioxidant Activity, Proportion of Dragon Fruit Peel Extract and Tomato Extract Abstrak Radikal bebas merupakan spesies reaktif yang dapat menyebabkan kerusakan pada jaringan tubuh bahkan menimbulkan banyak penyakit. Untuk menetralisir radikal bebas dalam tubuh diperlukan antioksidan. Banyak buah-buahan yang terdapat di Indonesia yang mengandung antioksidan antara lain buah naga, kandungan antioksidan pada buah naga tergolong tinggi. Permen jelly merupakan makanan selingan yang cukup digemari terutama anak-anak. Pada umumnya rasa permen jelly diperoleh dari essence yang merupakan bahan kimia. Pada penelitian ini rasa permen jelly diperoleh dari kombinasi buah naga dan tomat. Perlakuan pada penelitian ini adalah perbandingan sari kulit buah naga dan sari tomat, meliputi: Sari kulit buah naga 100 g + 0 g sari tomat (A); Sari kulit buah naga 25 g + 75 g sari tomat (B); Sari kulit buah naga 50 + 50 g sari tomat (C); Sari kulit buah naga 75 g + 25 g sari tomat (D); Sari kulit buah naga 0 g + 100 g sari tomat (E). Hasil penelitian bahwa proporsi sari kulit buah naga 100 g dan sari buah tomat 0 g mengandung total fenol paling tinggi pada permen jelly yaitu 15,2 mg GAE/g sampel. Aktivitas antioksidan berdasar pengujian DPPH paling kuat terdapat pada formula pencampuran sari kulit buah naga 0 g dan 100 g sari buah tomat dengan IC50 = 203,69 ppm. Permen jelly dengan proporsi 100 g sari kulit buah naga dan sari buah tomat 0 g mengandung vitamin C tertinggi sebesar 0,455 mg/100 g sampel. Kata Kunci: Permen Jelly, Aktivitas Antioksidan, Proporsi Sari Kulit Buah Naga dan Sari Tomat